2020
DOI: 10.1097/scs.0000000000006421
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Reconstruction of Complex Oncologic Scalp Defects in the Setting of Mesh Cranioplasty: Risk Factors and Outcomes

Abstract: Introduction: Soft-tissue reconstruction of the scalp has traditionally been challenging in oncologic patients. Invasive tumors can compromise the calvarium, necessitating alloplastic cranioplasty. Titanium mesh is the most common alloplastic material, but concerns of compromise of soft-tissue coverage have introduced hesitancy in utilization. The authors aim to identify prognostic factors associated with free-flap failure in the context of underlying titanium mesh in scalp oncology patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
0
22
2
Order By: Relevance
“…Yet, the current literature surrounding concurrent soft tissue reconstruction with cranioplasty is limited to single institution cohort studies, case studies, and case reports. 18–23,35–37 In the present study, the majority of composite microvascular scalp reconstructions were with muscle flaps (56.3%, n = 18), followed by fasciocutaneous flaps (25%, n = 8) and pedicled myocutaneous/fasciocutaneous flaps (18.7%, n = 6). In our study, there was no statistically significant difference in overall complication between flap type (37.5% versus 15.6%, P = 0.89).…”
Section: Discussionmentioning
confidence: 51%
“…Yet, the current literature surrounding concurrent soft tissue reconstruction with cranioplasty is limited to single institution cohort studies, case studies, and case reports. 18–23,35–37 In the present study, the majority of composite microvascular scalp reconstructions were with muscle flaps (56.3%, n = 18), followed by fasciocutaneous flaps (25%, n = 8) and pedicled myocutaneous/fasciocutaneous flaps (18.7%, n = 6). In our study, there was no statistically significant difference in overall complication between flap type (37.5% versus 15.6%, P = 0.89).…”
Section: Discussionmentioning
confidence: 51%
“…Although the mesh is efficacious for this purpose, previous studies have determined that underlying mesh in the setting of scalp reconstruction increases the risk for wound complications [ 27 , 28 ] This study also showed that titanium mesh increases not only the risk of complications, but also the propensity for the need for reoperation. We hypothesize that the presence of underlying mesh can compromise the underlying blood supply, which is critical for flap survival and flap efficacy [ 27 - 29 ]. This may consequently predispose ischemic tension, wound complications, and, ultimately, coverage failure, resulting in mesh exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of soft tissue and bony reconstruction has also been under debate. Previous studies have described soft tissue only reconstruction of composite defects, with the potential for delayed bony reconstruction depending on healing outcomes [46,48] . However, this approach leaves patients vulnerable to cerebral injury and development of the syndrome of the trephined, in which soft-tissue sinking over time leads to neurological dysfunction including cognitive, motor and language deficits [46] .…”
Section: Free Tissue Transfer and 3d Modelingmentioning
confidence: 99%
“…Their study, however, did not compare delayed or no cranioplasty to simultaneous reconstructions, and reported a fairly high complication rate of 29.2%. Kwiecien et al [48] , when evaluating re-infection rates of alloplastic cranioplasties performed for chronic cranial osteomyelitis, found a significantly higher rate if cranioplasties were performed earlier than 3 months after resection as compared to 1 year after resection. Given that perioperative radiation has been shown to be an independent predictor of post-free tissue transfer wound breakdown and associated infection [49] , many authors advise proceeding with caution if performing an alloplastic cranial reconstruction at the time of free tissue transfer in a previously radiated or infected surgical field [42,46,48,50] .…”
Section: Free Tissue Transfer and 3d Modelingmentioning
confidence: 99%